FELINE CLAMYDIOSIS IN DOMESTIC CATS - Divina Gracia Aviela; I Putu Gede Yudhi Arjentinia; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
A common conjunctival disease in kittens is Chlamydiosis. Chlamydia bacteria invade and infect the cells of the conjunctiva causing inflammation and eye discharge. Clinical signs develop within a few days of infection and begin with eye discharge. The aim of this article is to improve the knowledge of veterinary colleagues in managing cases of conjunctivitis in kittens caused by chlamydial bacterial infection. A 5-month-old female local cat weighing 1.6 kg named Chips had complaints of eye swelling, eye redness and continuous tear and eye discharge since it was adopted. The cat showed signs of difficulty opening the eyes. The diagnosis was confirmed by haematology and cytology examination. Cytological examination of the eye discharge swab was positive for Chlamydophila felis. Haematological examination showed leukocytosis, lymphocytosis and thrombocytopenia. The cat was diagnosed with Feline Chlamydiosis. The cat was treated with Erlamycetin Plus Eye Drop (Chloramphenicol and Dexamethasone) one drop twice daily for 14 days. Supportive therapy with immunomodulator Echinacea purpurea (Imboost Kids Syrup 60 ml) was given twice daily for 2.5 ml for 14 days. The therapy showed satisfactory results. On day 14 the cat was declared cured after therapy and routine eye cleaning. It can be concluded that cats with Chlamydiosis can be treated until cured using topical antibiotics and immunomodulators. The importance of early detection and owner understanding of good and healthy environmental conditions to prevent recurrent infections.